High‐Efficiency Semi‐Transparent Organic Solar Cells Using Pentacyclic Aromatic Lactam‐Containing Terpolymer Strategy for Eco‐Friendly Greenhouse Application. Issue 12 (11th October 2022) - Luo, Yixuan; Wang, Xunchang; Zhang, Manxue; Sun, Xiaokang; Saparbaev, Aziz; Lei, Shiyun; Zhang, Jiayi; Xiao, Biao; Yang, Chunming; Liu, Zhitian; Yang, Renqiang
Abstract : Semitransparent organic solar cells (ST‐OSCs) offer unique features such as spectral tunability and see‐through function, giving them great potential in photovoltaic (PV) agriculture. However, the combination of sufficient average visible transmittance (AVT) and high power conversion efficiency (PCE) with eco‐friendly device fabrication has always been a key issue. Herein, a simple but effective strategy by incorporating pentacyclic aromatic lactam acceptor unit (TPTI) in copolymer donors for toluene processed high‐efficiency ST‐OSCs is performed. The comparisons between D18‐ and DEH‐X‐based ST‐OSCs demonstrate the effect of TPTI inserting on the polymer main skeleton can not only lower the energy level, improve the processability in nonhalogen solvent, tune the ideal morphology for efficient charge dissociation, but also control a photon transport window suitable for plant absorption. Therefore, the resulting OSCs processed with toluene exhibit a PCE of 14.6% with an AVT of 22%, which represents one of the highest values for ST‐OSCs made from nonhalogenated solvents. What's more, it is found that plant growth under ST‐OSCs filtered light is comparable with that under natural light. Herein, a guide for developing high‐performance ST‐OSCs is provided and the prospect of ST‐OSCs for green manufacturing PV greenhouse application is demonstrated. Abstract : The copolymerization strategy with a pentacyclic aromatic lactam acceptor unit integration is used to improve the device processability in nonhalogen solvents, resulting in semitransparent organic solar cells (ST‐OSCs) with a maximum power conversion efficiency of 14.6%, an average visible transmittance of 22.5%, and a plant growth factor of 26%, making them one of the best‐performing ST‐OSCs for photovoltaic greenhouse applications.